Chronic Absenteeism in the Classroom Context: Effects on Achievement. (January 2019) - Gottfried, Michael A.
Although educational policy makers uphold that chronic absenteeism (missing 10% or more of the school year) is damaging to students' schooling outcomes, there is little empirical research to match. This study considers the role of spillover effects of chronic absenteeism on classmates' achievement. It does so by utilizing a large-scale administrative urban district data set of elementary schoolchildren—a sample of students where the rates of chronic absenteeism are expected to be higher compared with the national average. The results show that students suffer academically from having chronically absent classmates—as exhibited across both reading and math testing outcomes. Chronic absenteeism not only had a damaging effect on those individuals missing excessive school days but also has the potential to reduce outcomes for others in the same educational setting.